VISUALIZAÇÃO CARTOGRÃFICA: O AVANÇO DA CARTOGRAFIA DIGITAL (Boletim de Geografia, 2011)
An important evolution in digital cartography has taken place during the 1990's. After many years of the development of computer tools for digital cartography, primarily designed to automate the traditional methods of producing topographic maps, the early 1990's saw a significam change in digital map concepts. With the new understanding that computer tools can be employed by map users for generating and transforming maps, and that these maps can be seen as visual analysis tools, an important advance in digital cartography has taken place. If a user car ,H>ose a phenomenon to be visualized, and define the classification and symbology to uepict the phenomenon on a computer screen, this map is called an interactive map. When a user can interact with a map, map use is broader then communication, the user is no longer just a passive receiver of geographic information but can explore data in order to understanding rcality, and the map is transformed into a computer interface between the user and the real world. The exploration of geographic information using computer tools is similar to the exploration of data through scientific visualization tools. The results of studies and research in the areas of scientific visualization, computer graphics and geographic database concepts and techniques in digital cartography is called cartographie visualization or geographic visualization. This paper describes basic concepts about cartographie visualization and interactive maps, and is designed to present the potential contributions of digital cartography in education, planning and scientific research.